Pengembangan Training Kits Pengukuran Listrik Sebagai Media Pembelajaran pada Mata Pelajaran Memahami Pengukuran Komponen Elektronika di SMK Muhammadiyah 1 Padang - Darwin Alfasimi; Krismadinata Krismadinata; Sukardi Sukardi; Syukhri Syukhri (invotek, 2018)
Abstract—This study aims to develop training kits Measurement of electricity is valid, practical, and effective On the subject MPKE Class X TITL at SMK Muhammadiyah 1 padang The method used is research and development. The subject of this study is learning media Training Kits measurement of electricity and respondents are students of class X TITL 1 SMK Muhammadiyah 1 Padang and subject teachers MPKE SMK Muhammadiyah 1 Padang. Based on the research results obtained the validity from validator team that validation result with validator valid category. Test effective obtained from the results of classical completeness Seen from student learning outcomes. Posttest result of students who passed above KKM 21 students from 28 students Student scores below KKM 7 students, then the result of the 28 students who follow posttes 21 students graduated 21 students who graduated, Being in the effective category. Based on this research can be concluded that Training Kits is valid practical, and effective use to teach on subjects MPKE and can increase students' interest in learning so that it can bring the impact of increasing student learning outcomes.